(untitled) (Global Journal of Science Frontier Research, 2018)
The study was conducted in the late spring and early summer of 2017, in a foothill area of the Balkan Mountains, at an altitude of 386 m. We observed the ethological reactions of female calves of ’Bulgarian Rhodope Cattle’ and ’Montbeliarde’ breeds in the conditions of an artificial pasture. Two technological groups of animals were observed (six female calves intended for breeding), at the same age (180 days) and live weight of calves (107 kg on average for ’Bulgarian Rhodope Cattle’ and 129 kg of ’Montbeliarde’ breeds) by the method of analogs. Female calves of ’Bulgarian Rhodope Cattle’ used 17.7% (436 min) of their time within twenty-four hours for grazing and animals of ’Montbeliarde’ – 18.6% (453.24 min). For a 24-hour period, the animals of ‘Bulgarian Rhodope Cattle’ spent in a standing (187.5 min) and lying (523.3 min) position by 8.1 and 32.0 min more time in comparison with ’Montbeliarde’ breed. The terrain, abiotic factors, and the available grassland had an impact on the quality and quantity of grazing, hence the ethological reactions of the calves.